Creating shared value to get social license to operate in the extractive industry : a framework for managing and achieving the social license to operate - Saenz, Cesar (Emerald points., 2021)
No matter how hard employees work, an organization is in real trouble if strategic decisions are not made effectively. Doing the right things (effectiveness) is more important than doing things right (efficiency). Creating Shared Value to get Social License to Operate in the Extractive Industry showcases concepts and tools to make strategic decisions that determine the future direction and competitive position of extractive company enterprises to create shared value to earn SLO. Exploring a challenging and exciting keystone topic, Creating Shared Value to get Social License to Operate in the Extractive Industry presents techniques and models that will enable you to actually formulate, implement, and evaluate strategies to shared value to earn SLO.